Systematics and paleoecology of a new species of Varunidae H. Milne Edwards, 1853 (Decapoda: Brachyura) from the lower Eocene of Spain. Issue 2 (6th April 2022) - Ferratges, Fernando A; Zamora, Samuel; Aurell, Marcos
Abstract: The Roda Formation (early Eocene Ypresian, Huesca, Aragón, northern Spain) records successive levels including rich decapod faunas relevant for the understanding of Ypresian decapod assemblages. Asthenognathus fernandezi n. sp. is described from one of these levels, representing the oldest report of a fossil Asthenognathinae, and the first report from the Iberian Peninsula. Fossil members of Asthenognathinae Stimpson, 1858, are difficult to distinguish from other families, especially when they lack preserved pereiopods, sternum, and abdomen. The new taxon shows important features that include reduced pereiopods, small and sub-cylindrical carapace, and absence of protruding ornamentation. This combination of characters indicates a possible early adaptation of Asthenognathus Stimpson, 1858 to life in cylindrical cavities. Asthenognathus fernandezi n. sp. occurred on poorly consolidated siliciclastic substrates associated with a rich benthic fauna, including echinoderms, molluscs, and other crustaceans.